2006
DOI: 10.1093/jnci/djj244
|View full text |Cite
|
Sign up to set email alerts
|

A Cohort Study of Thyroid Cancer and Other Thyroid Diseases After the Chornobyl Accident: Thyroid Cancer in Ukraine Detected During First Screening

Abstract: Exposure to radioactive iodine was strongly associated with increased risk of thyroid cancer among those exposed as children and adolescents. In the absence of Chornobyl radiation, 11.2 thyroid cancer cases would have been expected compared with the 45 observed, i.e., a reduction of 75% (95% CI = 50% to 93%). The study also provides quantitative risk estimates minimally confounded by any screening effects. Caution should be exercised in generalizing these results to any future similar accidents because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
184
3
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(205 citation statements)
references
References 22 publications
15
184
3
3
Order By: Relevance
“…One cohort study using individual thyroid dose estimates has also been reported. That study found a significant association between estimated thyroid dose and thyroid cancer risk in a Ukrainian cohort of about 13,500 persons who were less than 18 years old at the time of the accident (20).…”
Section: Introductionmentioning
confidence: 91%
“…One cohort study using individual thyroid dose estimates has also been reported. That study found a significant association between estimated thyroid dose and thyroid cancer risk in a Ukrainian cohort of about 13,500 persons who were less than 18 years old at the time of the accident (20).…”
Section: Introductionmentioning
confidence: 91%
“…This is also reviewed in a paper in this Special Edition by Thomas et During the first screening in 1998-2000, 45 thyroid cancers were detected in Ukraine [52].…”
Section: Major Medical and Epidemiological Studies Of The Chernobyl Amentioning
confidence: 99%
“…To obtain the required baseline data, the present baseline survey was instituted by the FHM body, which was completed within three years of the Fukushima accident. It is unlikely that symptoms of thyroid cancer due to radiation had developed before this time point partly because an increase in thyroid cancer was reported to start only four to five years after the Chernobyl accident [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%